Marksman in the 21st century - Abdul Aziz Zainal General Tan Sri Dato' Seri Dr (Kementerian Pertahanan Malaysia, 2008)
Marksman is an idea promulgated initially by the Malaysian Army as the target of achievement for all its personnel. It aims to regenerate the core values of organisation and express them in the day-to-day routine of individuals and the organisation.